Medical students' knowledge, abilities and access characteristics to the internet at a peruvian university - Horna, Pedro (2002)
Objectives: To study the knowledge abilities and access characteristics to the Internet in undergraduate medical students from a Peruvian University. Methods: Development and application of a questionnaire to medical students, report of the results and nested case-control analysis of data to identify variables related to the ability to surf the Internet. Results: The students enter the Internet mainly from home. The most visited websites were those from web mail services and entertainment sites. The quality of the medical information available on the net was overrated, even though there was a poor knowledge of the online tools related to health, as well as a deficient ability with basic tools of navigation and e-mail. Being skillful on the Internet was significantly related to a long experience on the net, the presence of access to the Internet from home and the frequent use of e-mail and the WWW. Conclusions: The population studied does not have the ability and knowledge required to make the Internet a useful tool for its academic formation.